Quality of Drinking Water from Springs in Palestine: West Bank as a Case Study. (23rd June 2019) - Daghara, Azza; Al-Khatib, Issam A.; Al-Jabari, Maher
Abstract : The shortage of fresh water creates acute challenges in the West Bank of Palestine. Springs provide a main water resource in the West Bank. Investigating springs' water quality is essential step for promoting their public use. The aim of this research is to assess the microbiological and physiochemical quality parameters of drinking water from springs. The study methodology included sampling through field work and laboratory testing for water quality parameters using standard procedures. The study area covered all locations containing licensed springs by the Palestinian Water Authority in the West Bank of Palestine. The number of collected samples was 127 covering 300 springs. The chemical, physical, and biological parameters for each sample were measured. Then, the obtained characteristics were evaluated based on national and international quality standards (PSI and WHO). The investigated parameters included temperature, pH, EC, total hardness, concentrations of nitrate, sodium ions, total chlorine, residual chlorine, turbidity, and total and faecal coliforms. Most of investigated physical and chemical parameters were within the acceptable standard limits. However, the turbidity and chloride and nitrate concentrations exceeded standard limits. The findings indicate that only a minor fraction of the samples (2%) requires chlorination treatment, while most of the springs (97% of samples) are classified as possessing no risk.